A taxonomic revision of Swertia L. (Gentianaceae) in South India, with one new species and seven lectotypifications - Nampy, Santhosh; P.m., Shahina; T, Haseena; H.s., Ashwini (Phytotaxa, 2015)
The genus Swertia in South India is revisited based on field and herbarium studies. A brief history of the genus, detailed descriptions, photo plates, nomenclature, distribution and key to the identification of south Indian species are provided. Seven names viz., Swertia beddomei, S. trichotoma, S. affinis, S. lawii, S. minor, Ophelia elegans and O. umbellata are lectotypified. A new species, Swertia raveendrae, endemic to South India is also described here. The new species is similar to S. lawii but differs by its cordate-orbicular leaves, dense paniculate cymes, small (0.3–1 cm long), ovate-elliptic bracts and the calyx not exceeding the corolla in bud.